2015
DOI: 10.1158/0008-5472.can-14-2956
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant Expression of MHC Class II in Melanoma Attracts Inflammatory Tumor-Specific CD4+ T- Cells, Which Dampen CD8+ T-cell Antitumor Reactivity

Abstract: In the absence of a local inflammatory response, expression of MHC class II molecules is restricted mainly to hematopoietic cells and thymus epithelium. However, certain tumors, such as melanoma, may acquire aberrant constitutive expression of MHC class II. In a set of primary melanoma cell populations and correspondingly expanded autologous tumor-infiltrating lymphocytes (

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
89
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 100 publications
(96 citation statements)
references
References 44 publications
5
89
1
1
Order By: Relevance
“…Additionally, a high proportion of both CD4 + and CD8 + T cells expressed CD28, associated with an early or intermediate phenotype of the TILs [25]. To our knowledge, it is not well established to what extent the culture process used for generating T cells for current ACT protocols affects the phenotype or functionality of TILs, though we recently reported that the relative distribution of T cells expressing known antitumor functions seems maintained at stable levels [26]. Several groups have, however, reported that the tumour microenvironment induces T cell unresponsiveness towards tumour cells, which is apparent by high T cell expression of inhibitory markers [17], [20], [27], which could point to a similarity between the phenotype of tumour infiltrating lymphocytes in vivo and after expansion in vitro .…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, a high proportion of both CD4 + and CD8 + T cells expressed CD28, associated with an early or intermediate phenotype of the TILs [25]. To our knowledge, it is not well established to what extent the culture process used for generating T cells for current ACT protocols affects the phenotype or functionality of TILs, though we recently reported that the relative distribution of T cells expressing known antitumor functions seems maintained at stable levels [26]. Several groups have, however, reported that the tumour microenvironment induces T cell unresponsiveness towards tumour cells, which is apparent by high T cell expression of inhibitory markers [17], [20], [27], which could point to a similarity between the phenotype of tumour infiltrating lymphocytes in vivo and after expansion in vitro .…”
Section: Discussionmentioning
confidence: 99%
“…The expression of HLA class II has been suggested to represent an immune escape mechanism for melanoma. 45 The retargeting of CD8 C CTLs with HLA class II restricted TCRs may counter this mechanism of tumor escape. TCRs C13 and D71 recognized epitopes naturally processed from a 173 aa hTERT fragment, as described above.…”
Section: Discussionmentioning
confidence: 99%
“…In two cases, one patient with CR (M42) and one patient with no evidence of tumor regression (M40) where autologous melanoma cell lines were not available, single-cell suspensions obtained from enzymatically digested tumor fragments were used in antitumor reactivity assays (standard digestion protocol, as described previously; ref. 30). In all other cases where autologous tumor cell lines were not available, TILs were tested against multiple (5-12) HLA-A-matched allogeneic melanoma cell lines, and the highest level of reactivity to any of the cell lines was reported.…”
Section: Immunologic Analysesmentioning
confidence: 99%